2014
DOI: 10.1002/hec.3080
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Misclassification Error in Disability Rates

Abstract: This paper examines misclassification error in survey estimates of disability. The results suggest that a significant number of those with a disability fail to be recorded as such in the British Household Panel Survey. In addition, the probability of a false positive is estimated as being very close to zero in all demographic groups. There is a strong bias in estimates of differences in rates of disability across groups but only a small effect on estimates of the difference in employment by disability status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 17 publications
2
13
1
Order By: Relevance
“…That misclassification is a significant concern when assessing both disability status and labor market outcomes is not new. In terms of disability, Kreider and Pepper (2007, p. 432) note that “there is widespread concern about the accuracy of self‐reported disability status in survey datasets.” Gosling and Saloniki (2014, p. 1085) find a “strong estimated bias” in the employment gap between the non‐disabled and the disabled using a self‐reported measure of disability status similar to ours. This misclassification reflects many underlying causes, the most obvious which is a lack of an agreed‐upon definition of disability and a corresponding appropriately worded survey question, leading to subjectiveness in the understanding of concepts such as disability or work limitation (Baker et al., 2004; Hale, 2001).…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…That misclassification is a significant concern when assessing both disability status and labor market outcomes is not new. In terms of disability, Kreider and Pepper (2007, p. 432) note that “there is widespread concern about the accuracy of self‐reported disability status in survey datasets.” Gosling and Saloniki (2014, p. 1085) find a “strong estimated bias” in the employment gap between the non‐disabled and the disabled using a self‐reported measure of disability status similar to ours. This misclassification reflects many underlying causes, the most obvious which is a lack of an agreed‐upon definition of disability and a corresponding appropriately worded survey question, leading to subjectiveness in the understanding of concepts such as disability or work limitation (Baker et al., 2004; Hale, 2001).…”
Section: Introductionsupporting
confidence: 80%
“…14 Supplementary Figure A12 reveals that the unemployment gap can no longer be signed if Q exceeds roughly 0.05 in all years even under our most stringent assumptions. 15 It is difficult to report a precise comparison from Gosling and Saloniki (2014) since they report separate estimates of the gap by gender, schooling, and age. That said, the estimated gaps are below roughly 0.60 only for young females with no education qualifications.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Benítez-Silva et al (2004, p.649) are "unable to reject the hypothesis that self-reported disability is an unbiased indicator", while in contrast, Baker et al (2004Baker et al ( , p.1090 find "evidence that the error in self-reported chronic conditions is related to labor market status", and the results in Kerkhofs (2009, p.1042) "show that justification bias is substantial and that failing to account for this may change estimation results considerably". Further recent evidence on the importance of justification bias can be found in Gannon (2009), Datta Gupta and Larsen (2010), Datta Gupta and Jürges (2012), and Gosling and Saloniki (2014).…”
Section: Introductionmentioning
confidence: 90%
“…By replicating prior studies, the authors showed that key estimated parameters varied by up to 100% due to data errors. Other papers also indicated errors in aggregate statistical data for suicide [14], disability [15], mortality [16], and life satisfaction [17]. Thus, despite the fact that many studies have examined methods of correcting classification bias [9], [11], we can conclude based on previously mentioned cases that it is essential to analyze this bias together with a mathematical formula 1 for calculating the indicator for social indicators research.…”
Section: Introductionmentioning
confidence: 99%